Geographic variation in genetic composition, sexual communication and mating compatibility of the False Codling Moth, Thaumatotibia leucotreta for optimisation of area-wide control - Aigbedion-Atalor, Pascal; Heiduk, Annemarie; Upfold, Jennifer; Shuttleworth, Adam; Moore, Sean; Hill, Martin; Coombes, Candice (Frontiers in Ecology and Evolution, 2024)
Intraspecific variation in sex pheromones is a driver of reproductive isolation and speciation in insects. The False Codling Moth (FCM) Thaumatotibia leucotreta (Lepidoptera: Tortricidae) is a quarantine pest endemic to sub-Saharan Africa (SSA). The currently available precision control measures for FCM use female sex pheromone components to lure males into traps. However, the existing data on the composition of the female sex pheromone, especially the isomer ratios of the main pheromone component (E/Z)-8-dodecenyl acetate, are inconsistent for populations in SSA. This inconsistency led to speculation about possible reproductive isolation between geographically separated FCM populations and the potential need for local adjustment of pheromone-based FCM control tools. This, however, requires a comparative evaluation of geographic variation in FCM sexual communication and inter-population mating compatibility. We therefore investigated genetic isolation and mating compatibility between five geographically isolated FCM populations in South Africa and analysed the ratio of (E)- and (Z)-8-dodecenyl acetate in females from these populations. The five studied populations were found to form three genetically distinct groups with high genetic distances between each other. Mating compatibility tests showed that mating is possible across these groups, however, males preferred females of their own population when given choices; without a choice, males successfully mated with and transferred spermatophores to females from all other populations. The ratio of (E)- and (Z)-8-dodecenyl acetate was similar (c. 4:1) across the populations, indicating that this main female pheromone component does not cause the observed intra-population mating preferences. It remains to be investigated if qualitative/quantitative variation in other sex pheromone components influences intra-population recognition in South African FCM, providing a base for the development of regionally-specific lures for area-wide control programmes.